(untitled) (Plant Tissue Culture and Biotechnology, 2012)
Random Amplified Polymorphic DNA (RAPD) markers were used to study the molecular genetic diversity analysis among six BARI released lentil varieties viz. BARI masur-1, BARI masur-2, BARI masur-3, BARI masur-4, BARI masur-5 and BARI masur-6. PCR amplified products were visualized on 1.0% agarose gel and the band for each primer were scored. Ten RAPD markers were used in this study. Out of them 7 primers showed amplification of 53 DNA fragments with 60.37% of them being polymorphic. The highest number of polymorphic loci was noticed in the variety BARI masur-3. The same variety also showed maximum Neis gene diversity value (0.0552). The highest Neis genetic distance (0.5002) was observed in BARI masur-1 vs. BARI masur-5 whereas, the lowest genetic distance (0.0692) was found in BARI masur-1 vs. BARI masur-2. The unweighted pair group method of arithmetic mean (UPGMA) dendrogram based on Neis genetic distance grouped the six cultivars into two main clusters. BARI masur-1, BARI masur-2 and BARI masur-3 were in cluster I and BARI masur-4, BARI masur-5 and BARI masur-6 were in cluster II. The cultivar BARI masur-4 was closest to the cultivar BARI masur-6 with the lowest genetic distance (0.0972) and the highest genetic distance (0.5002) was found between BARI masur-1 and BARI masur-5. The RAPD markers were found to be useful in molecular characterization of lentil varieties which could be utilized by the breeders for the improvement of lentil cultivars. DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11260 Plant Tissue Cult. & Biotech. 22(1): 51-58, 2012 (June)